Estimativa de capital humano para a economia brasileira de 1970 a 2010 - José Ronaldo de Castro Souza Júnior; Sandro Sacchet de Carvalho; Thaís Mendonça Barcellos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This study seeks to quantify the stock of human capital in the Brazilian economy from 1970 to 2010. We chose to use the IBGE Demographic Census microdata, because, contrary to what is done in other studies - which use fi xed rates of return for all periods and/or regions of the country - this study estimates different rates of return for each year and Brazilian microregions. From these results, it was also estimated the evolution of total factor productivity (TFP) between 1970 and 2010 taking into account the education level and hours worked per individual. The results show that, until the 2000s, increased schooling led to growth in human capital stock, but between 2000 and 2010, stock growth slowed and even decreased in per capita terms - mainly due to a fall in the returns to education. The growth accounting analysis shows that the signifi cant increase in education and human capital was not accompanied by an expansion of productivity, which was practically stagnant from 1970 to 2010.
10419/284854
Keywords: I25; I26; J24; O47; 330; human capital; mincer equation; returns to education